State work–family contexts and the wage gap by gender and parenthood. Issue 4 (14th April 2022) - Strader, Eiko
Abstract: Objective: This article examines the association between state‐level work–family resources and earnings disparities by gender and parenthood. Background: The wage gap between childless men and women in the United States has narrowed, but the gap between mothers and fathers remains robust. Gendered division of labor and reduced labor force participation of women around childbirth have been raised as underlying causes. In the absence of national support, some states and migrant domestic workers have been filling the care gap, but it is unclear whether these factors are associated with the wage gap. Method: Individual‐level data from the 2012 American Community Survey were merged with state‐level data collected for 2010. Multilevel linear regression models were used to explore variation in earnings across states, accounting for compositional differences and selection into the labor force. Results: Temporary Disability Insurance, which enables new birth mothers to take paid leave, was robustly associated with narrower gaps between mothers and fathers. Unpaid private‐sector leave expansion and more intensive globalization of domestic work were associated with narrower gender wage gaps among parents with lower education. Provision of Head Start supplemental funding was associated with narrower wage gaps between mothers and fathers with higher education. Conclusions: Although mothers earned more in states with more work–family resources, the wage gap remained mostly unchanged because fathers similarly earned more in states with better work–family context. Implications: The results reflect the fragmented and incomplete nature of work–family support in the United States and calls for more comprehensive intervention strategies to reduce the wage gap.